Factors affecting wear of composite resin denture teeth$a24-month results from a clinical study - Stober, Thomas; Geiger, Andreas; Rues, Stefan; Rammelsberg, Peter; Ohlmann, Brigitte (Clinical oral investigations, 2012)
The objectives of this study were to measure the occlusal wear of composite resin denture teeth in patients wearing a complete denture and to evaluate factors affecting wear. Fifty participants provided with complete dentures in at least one jaw were included. Gypsum casts were made from preliminary vinyl polysiloxane impressions 4 weeks after insertion, then after 6 (t 1), 12 (t 2), and 24 months (t 3). Three-hundred and three posterior denture teeth were evaluated after 24 months. Wear was measured indirectly, from the casts, by means of a three-dimensional laser scanner device. Sequential images of the occlusal surfaces were digitized and superimposed (occlusal matching). Statistical analysis was performed by the use of mixed regression models, with the patient being a random effect. Mean wear (median, interquartile range; micrometer) of the entire occlusal surface was 8 (19) at t 1, 18 (34) at t 2, and 40 (61) at t 3. Maximum vertical loss (median, interquartile range; micrometer) was 92 (112) at t 1, 146 (148) at t 2, and 226 (184) at t 3. The dental status of the opposing jaw and the nature of the opposing material significantly affected the wear of denture teeth at t 3. Gender, daily wearing time, jaw, and type of tooth had no significant effects on the extent of wear. Clinically relevant vertical loss of composite resin denture teeth occurs after 24 months. Considering the limitations of this study, wear of denture teeth was affected by dental status and opposing material. The results suggest that wear of composite resin denture teeth exceeds that of enamel.
Published online: 8 March 2011
Gesehen am 28.08.2020